Effect of soluble dietary fiber extracted from Lentinula edodes (Berk.) Pegler on lipid metabolism and liver protection in mice on high-fat diet - Guo, Kangxiao; Liu, Jing; Yao, Zihan; Tan, Zhoujin; Yang, Tao (Frontiers in Nutrition, 2025)
With the increasing annual production of Lentinula edodes, the residues of Lentinus edodes are mass produced and wasted every year. In order to further explore the added value and effective utilization of Lentinus edodes, we studied the lipid-lowering efficacy and liver protective effect of Lentinus edodes soluble dietary fiber in mice on high-fat diet. Project team from Lentinus edodes extracted soluble dietary fiber, and its physicochemical properties, selected 30 male mice, randomly divided into normal group (N), high fat diet group (F), add low dose dietary fiber high fat diet (FL), add medium dose dietary fiber high fat diet group (FM), add high dose dietary fiber high fat diet group (FH) five groups. After 4 weeks, we assessed general state, organ conditions, liver status, blood parameters, expression of hepatic lipid metabolism genes, mRNA levels of key hepatic lipid metabolism genes. The results showed that the molecular weight of soluble dietary fiber is about 17.029 kDa, and the monosaccharides such as galactose, glucose and mannitol are connected by β-glycosidic bond. The soluble dietary fiber of Lentinus edodes can effectively slow the weight growth due to high-fat diet, delay liver tissue lesions, reduce the levels of ALT, AST, ACP, LDL-C, TG, TV, FFA, SOD, GSH and MDA, and increase the levels of γ-GT, HDL-C and CAT in blood. Lentinus edodes soluble dietary fiber decreased the expression of AMPKα and SREBP-2 in the liver, and increased the expression of PPARα, ACS, CPT1a, CYP7A1. It is proved that the soluble dietary fiber of Lentinus edodes can alleviate the organ fat accumulation caused by high-fat diet to some extent, effectively combat the liver injury, oxidative stress pressure and lipid metabolism disorder caused by high-fat diet, and provide an experimental basis for the subsequent effective use of soluble dietary fiber of Lentinus edodes in fat reduction.